Computational Investigation of the Electronic and Optical Properties of Planar Ga-Doped Graphene - Nicole Creange; Costel Constantin; Jian-Xin Zhu; Alexander V. Balatsky; Jason T. Haraldsen (Advances in Condensed Matter Physics)
We simulate the optical and electrical responses in gallium-doped graphene. Using density functional theory with a local density approximation, we simulate the electronic band structure and show the effects of impurity doping (0–3.91%) in graphene on the electron density, refractive index, optical conductivity, and extinction coefficient for each doping percentage. Here, gallium atoms are placed randomly (using a 5-point average) throughout a 128-atom sheet of graphene. These calculations demonstrate the effects of hole doping due to direct atomic substitution, where it is found that a disruption in the electronic structure and electron density for small doping levels is due to impurity scattering of the electrons. However, the system continues to produce metallic or semimetallic behavior with increasing doping levels. These calculations are compared to a purely theoretical 100% Ga sheet for comparison of conductivity. Furthermore, we examine the change in the electronic band structure, where the introduction of gallium electronic bands produces a shift in the electron bands and dissolves the characteristic Dirac cone within graphene, which leads to better electron mobility.